1997
DOI: 10.1021/bi9626719
|View full text |Cite
|
Sign up to set email alerts
|

The Photosynthetic Oxygen Evolving Complex Requires Chloride for Its Redox State S2→S3 and S3→S0 Transitions But Not for S0→S1 or S1→S2 Transitions

Abstract: The Cl- requirement in the redox cycle of the oxygen-evolving complex (OEC) was determined by measurements of flash-induced UV absorbance changes in Cl(-)-depleted and Cl(-)-reconstituted photosystem II membranes. On the first flash after dark adaptation the spectrum and amplitude of those changes, known to reflect the oxidation of MnIII to MnIV on the S1-->S2 transition, were the same in the presence or absence of Cl-. On the second and later flashes, however, absorbance changes in Cl(-)-depleted samples reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 32 publications
11
145
2
1
Order By: Relevance
“…This suggestion is in line with the observed strong retardation of electron transfer between Y Z and P 680 + in Ca-depleted PSII (29,83,110). On the contrary, in Cl --depleted centers where electron transfer from Y Z to P 680 + occurs as fast as in controls, i.e., in nanoseconds (8), the difference spectrum Y Z ox -Y Z (8,111) is similar to the one measured in oxygen-evolving centers in the whole spectral region. This indicates a more similar environment of Y Z in oxygen-evolving and Cl --depleted centers.…”
Section: Discussionmentioning
confidence: 87%
“…This suggestion is in line with the observed strong retardation of electron transfer between Y Z and P 680 + in Ca-depleted PSII (29,83,110). On the contrary, in Cl --depleted centers where electron transfer from Y Z to P 680 + occurs as fast as in controls, i.e., in nanoseconds (8), the difference spectrum Y Z ox -Y Z (8,111) is similar to the one measured in oxygen-evolving centers in the whole spectral region. This indicates a more similar environment of Y Z in oxygen-evolving and Cl --depleted centers.…”
Section: Discussionmentioning
confidence: 87%
“…21 Recent studies have indicated that the presence of Cl is necessary only for the S 2 →S 3 and S 3 →S 0 transitions of the OEC, while the earlier steps of the cycle can proceed in its absence. 48,49 The amplitude and distance changes of Fourier peak III in the S 3 state are less obvious. Peak III appears substantially above the noise level in three of the six S 3 FTs and is readily distinguishable from the noise in two others.…”
Section: Exafs Of the S 3 Statementioning
confidence: 98%
“…Additionally, it is possible that chloride depletion perturbs a proton exit pathway (37). Such disruption could give rise to long-lived higher S states (38,39) that may increase the probability of the release of partially oxidized water intermediates. These possibilities are not mutually exclusive.…”
Section: Psii Electron Donor Side Ros Production By Incomplete Water mentioning
confidence: 99%